Experimental Cosserat elasticity in open-cell polymer foam. Issue 2 (12th January 2016) - Rueger, Zach; Lakes, Roderic S.
Abstract : Reticulated open-cell polymer foams exhibit substantial size effects in torsion and bending: slender specimens are more rigid than anticipated via classical elasticity. Such size effects are predicted by Cosserat (micropolar) elasticity, which allows points to rotate as well as translate and incorporates distributed moments (couple stresses). The Cosserat characteristic length is larger than the cell size. The Cosserat coupling coefficient is larger than in dense closed-cell foams and approaches 1 for foam with 0.4 mm cells.